Teachers’ PCK and Pedagogical Decisions in English Materials Design at Junior High School Tahfidz Entrepreneur Khairunnas Tuban - Alfi Az Zuhriyah; Irmayani; Buyun Khulel; Syifa Khuriyatuz Zahro (Universitas Nahdatul Ulama Surabaya, 2026)
In the context of rapidly evolving educational demands and increasing integration of digital technologies, teachers are required to make informed and adaptive pedagogical decisions in designing effective learning materials. Understanding how these decisions are shaped is essential to improving English language teaching at the junior secondary school level. This study aims to explore and describe teachers’ Pedagogical Decision Making in designing English learning materials through the perspective of Pedagogical Content Knowledge (PCK). Using a descriptive qualitative approach, the study collected data through in-depth interviews with English teachers, which were further triangulated with students’ perceptions to ensure data validity and richness. The findings reveal that teachers’ pedagogical decisions in material design are not simple tasks but complex processes shaped by their knowledge of learners’ characteristics, curriculum demands, available resources, sociocultural context, and the growing integration of educational technology. Teachers consistently adjust the linguistic complexity of texts, select contextually relevant topics, and apply various scaffolding strategies to support students in overcoming linguistic limitations. In addition, teachers must balance the use of standardized textbooks with the need to modify materials to align with core competencies and students’ profiles. The study also highlights that emotional and motivational factors play an essential role in decision-making, particularly in maintaining students’ engagement and confidence. These results suggest that teachers’ PCK is dynamic and continuously evolving through reflection, teaching experience, and responsiveness to classroom realities. Therefore, the study recommends the implementation of more systematic and sustained professional development programs focusing on material design, PCK enhancement, and digital literacy. Such initiatives are crucial to empower teachers in creating English learning materials that are contextual, innovative, and responsive to the diverse needs of contemporary learners.